Effect of IPL in Patients with Meibomian Gland Dysfunction - Schuh, Anna; Muth, Daniel; Shajari, Mehdi; Mayer, Wolfgang J.; Priglinger, Siegfried; Messmer, Elisabeth (Klinische Monatsblätter für Augenheilkunde, 2021)
Purpose To evaluate the effect of IPL (intense pulsed light) treatment in patients with meibomian gland dysfunction (MGD).Methods Clinical data of 25 patients with MGD who underwent IPL treatment at the department of ophthalmology of Ludwig-Maximilians-University between 2016 and 2018 were analyzed. Demographics, clinical history, examination findings (eyelid vascularization, meibomian gland findings, conjunctival redness, tear film break-up time [TFBUT], corneal staining (Oxford grading scale [OGS]), and subjective patientsʼ findings (including ocular surface disease index [OSDI]) were collected from each visit (D1, D15, D45, D75).Results All included patients underwent three sessions of IPL treatment in both eyes (D1, D15, D45). There was a significant improvement after IPL treatment (D75) in TFBUT (p < 0.001), corneal staining (OGS) (p < 0.001), conjunctival redness (p < 0.001), lid margin edema (p < 0.001) and redness (p < 0.001), meibum quality (p < 0.001), lid margin telangiectasia (p = 0.005), meibomian gland obstruction (p = 0.001), and OSDI score (p = 0.004). Even after the first IPL session, significant improvements in TFBUT (p < 0.001), corneal staining (OGS p < 0.001), conjunctival redness (p < 0.022), lid margin edema (p < 0.001) and redness (p < 0.016), meibum quality (p = 0.014), and OSDI score (p < 0.013) were noted. There were no relevant negative side effects. Subgroup analysis for age, sex, duration or severity of disease, and associated diagnosis of rosacea showed no significant difference in effectiveness.Conclusion IPL is an effective and safe treatment for patients with MGD, which can be used as a supportive therapeutic option.
Keywords: IPL; Meibomian gland dysfunction; dry eye; light impulse; intensive pulsed light